Wear and Corrosion Resistance of Thick Ti-6Al-4V Coating Deposited on Ti-6Al-4V Substrate via High-Pressure Cold Spray - Khun, Nay Win (2017)
Ti-6Al-4V (Ti64) coating with a thickness of about 9 mm was deposited on commercial Ti64 substrate via a high-pressure cold spray process. The microstructure, hardness, and wear and corrosion resistance of the Ti64 coating were systematically investigated. The hardness of the Ti64 coating was higher than that of the Ti64 substrate due to the cold-worked microstructure of the coating. The tribological results showed that there was no significant difference in the surface wear rates of the Ti64 coating measured on its different layers while the surface wear resistance of the Ti64 coating was lower than its cross-sectional wear resistance. The corrosion results showed that the Ti64 coating did not effectively prevent its underlying Ti64 substrate from corrosion due to the occurrence of pores in the coating microstructure. It could be concluded that the hardness and wear resistance of the Ti64 coating were comparable to those of the commercial Ti64 substrate.